Laughter and Ethnicity in John Leguizamo’s One-Man Worlds - Chirico, Miriam M. (Latin American Theatre Review, 2002)
As the first Latino to produce a one-man show on Broadway, John Leguizamo is a spokesperson for a culture vying to be heard, and his dramatic sketches question the status quo of race relations in America. His plays Mambo Mouth, Spic-O-Rama, Freak, and Sexaholix . . . A Love Story reflect his training as a stand-up comedian and his investment in the social and political issues that shape Latino representation. Leguizamo depicts stereotypical Latino characters in an effort to attack ethnic prejudice, but his comedies are problematic. When he enacts racial stereotypes in front of a mixed audience of whites and Latinos, he seems to perpetuate negative images of Latinos in order to mock them. However, Leguizamo’s goal is to create "prototypes," characters whose cultural cues make them easily recognizable, and then to encourage people to see behind these characters’ masks. Rather than shun negative racial depictions, he renders them more human through their individual stories. (MMC)